Dynamics and patterns of land cover change in the Piura River Basin (Peruvian Pacific slope and coast) in the last two decades - Castillon Lucas, Fiorela V. (2025)
Land use and land cover (LULC) changes in the Piura River Basin, Peru, were analyzed from 2001 to 2022 using global MODIS and ESA-CCI datasets harmonized into six major land cover classes (Forest, Non-Forest Vegetation, Cropland, Bare Soil, Water and Urban) for comparative analysis. Pearson correlation analyses with hydroclimatic variables, including precipitation (PP), maximum (Tx) and minimum (Tn) temperatures, and El Niño Southern Oscillation (ENSO) indices (Eastern Pacific, Central Pacific, and Coastal El Niño), complemented the intensity analysis to explore environmental drivers. The analyses focused on the lower-middle and upper basin regions during wet (December-May) and dry (June-November) seasons. MODIS detected more dynamic LULC transitions, with 32.8% of pixels showing changes, compared to 6.8% detected by the ESA-CCI product. These differences reflect the distinct sensitivities of MODIS and ESA-CCI products to short-term fluctuations and long-term variations, respectively. Specifically, MODIS identified higher annual change intensities and more frequent transitions, especially in the upper basin, whereas ESA-CCI provided a more conservative view of land cover trends. Both datasets consistently indicated a decline in cropland areas and an increase in bare soil, suggesting agricultural degradation and potential desertification processes. Correlation analyses revealed significant relationships between vegetation dynamics and climatic variables, notably ENSO events, precipitation, and temperature extremes, highlighting how hydroclimatic factors drive vegetation variability. The upper basin experienced notable urban expansion and deforestation dynamics linked to temperature fluctuations and intensified El Niño events, particularly after 2011. These findings underscore the critical influence of climatic extremes and human activities on vegetation dynamics, emphasizing the need for integrated, adaptive management strategies to mitigate desertification in lowlands and enhance forest conservation in highlands.